(untitled) (The Review of Diabetic Studies, 2025)
Diabetes mellitus (DM) is one of the most pressing global health concerns of the 21st century, characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The limitations of existing pharmacological therapies, such as side effects, drug resistance, and high costs, have intensified the search for alternative and adjunctive therapeutic options. Phytochemicals—bioactive plant-derived compounds—have long been utilized in traditional medicine systems and are increasingly gaining attention as promising antidiabetic agents. These compounds, including flavonoids, alkaloids, terpenoids, and polyphenols, exert multifaceted antidiabetic effects, such as enhancing insulin sensitivity, promoting pancreatic β-cell regeneration, modulating glucose transport, inhibiting carbohydrate-digesting enzymes, and regulating oxidative stress and inflammation. Recent advances in phytochemistry, nanotechnology, molecular docking, and pharmacogenomics have deepened our understanding of these compounds, bridging traditional remedies with next-generation therapeutic approaches. Several phytochemicals, such as berberine, curcumin, resveratrol, quercetin, and ginsenosides, have progressed from bench research to preclinical and clinical evaluation, demonstrating favorable outcomes in glycemic control and metabolic regulation. Nevertheless, challenges persist, including poor bioavailability, variability in plant-derived preparations, safety concerns, and regulatory barriers. This review aims to provide a comprehensive update on recent advances in antidiabetic phytochemicals, critically analyzing their mechanisms of action, translational potential, and clinical applications. It also highlights innovations in drug delivery systems, synergistic combinations with conventional antidiabetic drugs, and the integration of artificial intelligence in phytochemical discovery. By bridging ethnopharmacological knowledge with modern drug development, phytochemicals may play a pivotal role in shaping future personalized therapies for diabetes management.